Радянський джентльмен: український професор супроти викликів історії - Blashkiv, Oksana (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2019)
The emphasis is placed on the main character’s personal, national and academic identity. A university professor and a linguist, the protagonist constructed his identity through combining the elements of Sovietness, Englishness, and Ukrainianness. While focusing on the protagonist’s identity quest, the author also identifies historical context of the novel, which is rooted in Ukrainian socio-historic reality throughout the 1950s-2010s.